Обратная задача теории решеток на осесимметричной поверхности тока - Субботович, Валерий Петрович; Юдин, Александр Юрьевич; Фан, Конг Там (НТУ "ХПИ", 2009)
The inverse problem about the three-dimensional flow in the blade channel on the surface which is the general surface of revolution was researched. The problem is researched as the one that consists of the independent problems of the flow’s calculation in the separated cross-section of the stream filament. These independent problems can be solved either one after another or simultaneously. The inverse problem allows to obtain a geometrical characteristics of blade profiles when limitations of aerodynamic and geometrical parameters
Keywords: турбостроение практическое; проектирование профилей; направляющие лопатки